"Explanation and Citicism of the Interpretation of Women's Readings of the Qur'an on "Justice as a Theological Basis for Interpretation" - Mohsen badreh; kosar mirzaei (پژوهش نامه معارف قرآنی, 2023)
Adl, as one of the theological foundations of reading the relationship between the two sexes from the perspective of the Holy Quran, has found a special place among Muslim women thinkers. In such a way that one of the main foundations of modern feminist readings of the Holy Qur'an is reliance on justice as a theological basis, new-thinking women consider the condemnation of femininity in traditional interpretations as a result of the centrality of hadiths in the interpretation of the Qur'an, the human mistakes of the commentators, and not considering the gradual approach of the Qur'an towards equality. Some Shiite mujtahids, by accepting the same human identity of both sexes, consider justice in adopting appropriate approaches to gender differences in the form of rights and duties, in individual, family, and social fields. In this context, neo-thinking women believe in egalitarian justice and Shia thinkers believe in meritorious justice. This research examines the justice between the two sexes in the Qur'an from the point of view of Shia thinkers and feminist readings using an analytical-applied method